Collagen prolyl 4-hydroxylase 1 is essential for HIF-1α stabilization and TNBC chemoresistance. Issue 1 (December 2018) - Xiong, Gaofeng; Stewart, Rachel; Chen, Jie; Gao, Tianyan; Scott, Timothy; Samayoa, Luis; O'Connor, Kathleen; Lane, Andrew; Xu, Ren
Abstract Collagen prolyl 4-hydroxylase (P4H) expression and collagen hydroxylation in cancer cells are necessary for breast cancer progression. Here, we show that P4H alpha 1 subunit (P4HA1) protein expression is induced in triple-negative breast cancer (TNBC) and HER2 positive breast cancer. By modulating alpha ketoglutarate (α-KG) and succinate levels P4HA1 expression reduces proline hydroxylation on hypoxia-inducible factor (HIF) 1α, enhancing its stability in cancer cells. Activation of the P4HA/HIF-1 axis enhances cancer cell stemness, accompanied by decreased oxidative phosphorylation and reactive oxygen species (ROS) levels. Inhibition of P4HA1 sensitizes TNBC to the chemotherapeutic agent docetaxel and doxorubicin in xenografts and patient-derived models. We also show that increased P4HA1 expression correlates with short relapse-free survival in TNBC patients who received chemotherapy. These results suggest that P4HA1 promotes chemoresistance by modulating HIF-1-dependent cancer cell stemness. Targeting collagen P4H is a promising strategy to inhibit tumor progression and sensitize TNBC to chemotherapeutic agents. Hyperactivation of HIF-1α is crucial in progression of triple-negative breast cancer, but how HIF-1α stability is maintained in a hypoxia-independent manner is unclear. Here, the authors show collagen prolyl-4-hydroylase 1 stabilises HIF-1α and is involved in chemoresistance in TNBC.